Helicobacter suis-Associated Gastritis Mimicking Conventional H. pylori-Associated Atrophic Gastritis - Masaya Iwamuro; Somay Yamagata Murayama; Masahiko Nakamura; Kenta Hamada; Takehiro Tanaka; Hiroyuki Okada (Case Reports in Gastrointestinal Medicine)
A 45-year-old Japanese man underwent esophagogastroduodenoscopy, which revealed spotty redness at the gastric fornix, mucosal swelling, diffuse redness in the corpus, and mucosal atrophy in the gastric angle and antrum. Histological examination showed rod-shaped bacteria that appeared larger than Helicobacter pylori. The patient tested positive for rapid urease test, and serum anti-H. pylori IgG antibody test results were negative. Further examination of the bacteria revealed that H. suis antibody test was positive, and the presence of H. suis was confirmed using H. suis-specific real-time PCR. H. suis was successfully eradicated after triple therapy with vonoprazan, amoxicillin, and clarithromycin. This case reinforces the notion that non-H. pylori Helicobacter species such as H. suis and H. heilmannii may be involved in the pathogenesis of active gastritis in patients who test negative for H. pylori antibodies.